Investigation of Association of Complement 5 Genetic Polymorphisms with Sepsis and Sepsis-Induced Inflammatory Responses - Chen K (Dove Medical Press, 2021)
Kaidian Chen,1,* Yao Lin,1,* Yuchun Liu,1,* Shuanglin Liao,2 Ruoxuan Yang,1 Jiefeng Huang,1 Mingwei Xu,1 Junbing He1 1The Intensive Care Unit, Jieyang Affiliated Hospital, Sun Yat-sen University, Jieyang, Guangdong, People’s Republic of China; 2The Intensive Care Unit, The First Dongguan Affiliated Hospital of Guangdong Medical University, Dongguan, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Junbing He; Mingwei XuThe Intensive Care Unit, Jieyang Affiliated Hospital, Sun Yat-sen University, Tianfu Road 107, Rongcheng district, Jieyang, 522000, Guangdong Province, People’s Republic of ChinaEmail junbinghe_gmc@163.com; mingweixu_gmc@126.comBackground: Complement 5 (C5) and C5a production play a pivotal role in the pathophysiology of sepsis. Strong evidence demonstrates an association of C5 gene polymorphisms with various inflammatory diseases. However, no current studies have explored the clinical relevance of C5 polymorphisms in sepsis.Methods: Two C5 gene polymorphisms, rs17611 and rs2269067, were identified by genotyping in 636 sepsis patients and 753 controls in a Han Chinese population. C5 gene expression was detected via quantitative real-time PCR. C5a and proinflammatory cytokine production was measured by enzyme-linked immunosorbent assay. An Annexin V apoptosis assay was performed to assess cell apoptosis.Results: Our results showed significantly lower frequencies of rs2269067 GC/CC genotypes or C allele in sepsis patients than healthy controls. The frequencies of rs17611 CC/CT genotypes or C allele were significantly overrepresented in both the septic shock and non-survivor subgroups. Patients with this sepsis-associated high-risk rs17611 C allele exhibited a significant increase in C5a, TNF-α and IL-6 production. However, no significant difference in C5a and downstream proinflammatory cytokine production was observed among patients with different rs2269067 genotypes. In addition, in vitro experiments showed an effect of recombinant C5a on enhancing LPS-stimulated IL-1β, IL-6 and TNF-α production and cell apoptosis in THP-1 monocytes.Conclusion: The rs2269067 polymorphism conferred protection against sepsis susceptibility. The rs17611 polymorphism was associated with increased C5a production, which ultimately potentiated the secretion of downstream proinflammatory cytokines and conferred susceptibility to sepsis progression and poor prognosis.Keywords: C5, C5a, polymorphism, sepsis, inflammation